2015
DOI: 10.1586/14760584.2015.1075884
|View full text |Cite
|
Sign up to set email alerts
|

The impact of 10-valent and 13-valent pneumococcal conjugate vaccines on serotype 19A invasive pneumococcal disease

Abstract: The circulation in the community of pneumococcal serotype 19A, a highly invasive and frequently extremely resistant pneumococcal strain, has increased the focus on methods to control its presence and effect. Two vaccines have been developed: the 10-valent pneumococcal conjugate vaccine (PCV10) and the 13-valent pneumococcal conjugate vaccine (PCV13). Available data indicate that PCV13 is highly effective in reducing the risk of serotype 19A invasive pneumococcal disease (IPD) in both vaccinated children and un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 36 publications
(21 reference statements)
1
15
0
Order By: Relevance
“…Moreover, as fluctuations in the frequency of the serotypes can occur without selective pressure of vaccines, and considering limitations in study design and small number of cases, it is not possible to attribute increases in non-vaccine serotypes to the reduction in vaccine-type circulation in a vaccinated population as pointed out by Hirose et al [19]. Reduction of carriage is fundamental to determine indirect and direct effects of pneumococcal vaccination with conjugate vaccines and it was highlighted in a systematic review where the reduction of risk on IPD due to 19A was discussed [61]. Additionally for robust conclusions it is important that countries implement surveillance, at least, to monitor the frequency of vaccine-type and non-vaccine type invasive pneumococcal disease in different age groups and for identification of factors influencing serotype distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as fluctuations in the frequency of the serotypes can occur without selective pressure of vaccines, and considering limitations in study design and small number of cases, it is not possible to attribute increases in non-vaccine serotypes to the reduction in vaccine-type circulation in a vaccinated population as pointed out by Hirose et al [19]. Reduction of carriage is fundamental to determine indirect and direct effects of pneumococcal vaccination with conjugate vaccines and it was highlighted in a systematic review where the reduction of risk on IPD due to 19A was discussed [61]. Additionally for robust conclusions it is important that countries implement surveillance, at least, to monitor the frequency of vaccine-type and non-vaccine type invasive pneumococcal disease in different age groups and for identification of factors influencing serotype distribution.…”
Section: Discussionmentioning
confidence: 99%
“…[73][74][75][76][77] PCV13 appeared efficient in preventing vaccine-type pneumococcal bacteraemia and non-bacteraemia CAP in the community-dwelling elderly population, as well as vaccine-type IPD, but not in preventing CAP from any cause. 26 PCV13 induced a higher immunological response (measured by OPA) than PPV23. 78 In addition, PPV23, followed 1 y later by PCV13 (PPSV23/PCV13), elicited significantly lower OPA titres than those produced after only an initial dose of PCV13 for all 13 serotypes.…”
Section: Pneumococcal Vaccinationmentioning
confidence: 84%
“…[23][24][25] In recent years, the age indication for PCV13 was first extended from subjects aged 5 y to include those aged 50 y, and subsequently further extended to include all ages based on comparative immunogenicity data, including also the 18-64 y age group. 26 In the comparison of opsonophagocytic activity (OPA) titres between subjects 60-64 y of age, vaccinated either with PCV13 or PPV23, superiority was demonstrated for PCV13 with 9 of 12 common serotypes and noninferiority for the remaining 3, whereas the comparison between younger subjects only immunized with PCV13 and subjects in the 60-64 y age group vaccinated with PCV13 demonstrated consistently higher titres in younger vaccines. 26 The meta-analysis conducted in the Cochrane review found strong evidence of PPV23 efficacy against invasive pneumococcal disease (IPD).…”
Section: Pneumococcal Vaccinationmentioning
confidence: 98%
See 2 more Smart Citations